The influence of non-pharmacological methods in osteoporosis treatment - Kujawska, Agnieszka; Gajos, Małgorzata; Topka, Weronika; Szmelcer, Beniamin; Bieniek, Daria; Modlińska, Aleksandra; Kożuchowski, Marcin; Perkowski, Radosław; Androsiuk-Perkowska, Joanna; Ziółkowska, Sylwia (Journal of Education, Health and Sport, 2019)
Introduction Osteoporosis is a systemic skeletal disorder which results from an imbalance in bone remodeling. The disease can occur because of failure to achieve peak bone mass and/or excessive bone resorption and/or decreased bone formation during remodelling. Multiple pathogenetic and regulatory mechanisms are responsible for these changes. In the above review, selected non-pharmacological therapies in osteoporosis are described. Material and methods Articles in the EBSCO database have been analyzed using keywords: osteoporosis, osteopenia, treatment. The available literature is subjectively selected. Then, the newest version of every paper was searched for. Results Results of researches on osteoporosis pathomechanism, quality of life in patients, comorbidities, non-pharmacological methods for treatment of osteoporosis, the impact of physical exercise, role of diet as adjunctive therapy in osteoporosis were described. Conclusions Osteoporosis and treatment influence on the patient’s functioning and subjective assessment of the quality of life. Medical doctors need to take into account high occurrence of multimorbidity in adults with osteoporosis to be able to propose comprehensive treatment. The treatment of the affected patients should be improved to offer early or even preventive care for other diseases that coexist with osteoporosis. Non-pharmacological interventions, such as diet, seem to be effective in osteoporosis. Effects of physical exercise could be beneficial in osteoporosis patients, however further studies are needed to determine specifics of the most effective program.